Minutes of the EURISCO Advisory Group and the ECP/GR documentation and information network coordinating group for the preparation of a PGR documentation project: Joint Meeting, 5 March 2004, Wageningen, The Netherlands - Menting, F.; European Cooperative Programme for Plant Genetic Resources (2005)
On January 27th, 2004 a meeting was held in Bonn to brainstorm about a project submission in the field of PGR documentation to the call for proposals for the new EU GENRES programme expected for spring 2004. The output of this brainstorming session was a list of items that could serve as building blocks for a PGR documentation project (appendix C). The objective of this meeting was to create, with a wider group of actors (EURISCO Advisory Group and ECP/GR Documentation and Information Network Coordinating Group), a consensus on collaborative actions that would be the basis for a project proposal to the EU GENRES programme. The meeting draft agenda (appendix A), list of participants with their contact details (appendix B) and the final report of the EPGRIS project were circulated.